ANALISIS ROASTING DALAM PRESPEKTIF DEMOKRASI (STUDI ROASTING-AN KIKIY SAPUTRI TERHADAP RIDWAN KAMIL DAN SANDIAGA UNO DI KANAL YOUTUBE INDOSIAR) - Muhamad yusup Rezeki Damuya (Jurnal Prodi Ilmu Politik, 2023)
The protection of freedom of opinion and expression helps ensure that citizens can provide oversight, criticism and ideas to the government, which is essential in a democratic republic. The delivery of criticism/opinion can be delivered in the form of humor/comedy which is a form of art and entertainment around the world. This research aims to analyze whether and how the roasted comedy phenomenon can be accessed on social media in Indonesia from a democratic point of view. The method used in this research is a qualitative method using an analytical descriptive approach with sources and data in the form of premier data, namely video footage of Kiky Saputri's roast of Ridwan Kamil and Sandiaga Uno at the Indosiar Anniversary event. The video footage was obtained from the Indosiar youtube channel. Meanwhile, secondary data consists of scientific journal articles and online content that can complement the work of researchers roasting Kiky Saputri, Ridwan Kamil and Sandiaga Uno. Physical data is documented using this research data collection method, while digital files including data obtained from the internet are collected and stored digitally. The research found that First, freedom of expression is the basis of democracy. Second, freedom of expression plays a role in the fight against corruption. Third, freedom of expression promotes accountability. Fourth, freedom of expression in society is believed to be the best way to find the truth.